Profile of Animal Ecology Field trip: Description of Studentsâ€™ Identification Skills and Classification Skills - Iwan Setia Kurniawan; Fransisca Sudargo Tapilouw; Topik Hidayat (Scientiae Educatia: Jurnal Pendidikan Sains, 2017)
This study aimed to describe the activities in the field trip of animal ecology course and describe the identification and classification skills of students at Animal Ecology course. Also, this study describes students responses on-field activities. This study uses a quasi-experimental method using only post-test design. Data analysis using quantitative descriptive analysis techniques. The research subject as many as 30 students to take the test and 40 students are given a questionnaire. The results showed that the CPL course and CPL subjects not relevant to the fact that in both CPL there are some points the use of science and technology, the reality in the learning process technology, it is also supported by student response on the issue. The identification and classification skills of students included in the category sufficient. Analysis of Pearson correlation between the identification and classification skills showed no significant relationship (-.107), it is contrary to some assumptions that states that the ability to identify a basis for classification capability. Thus the results of this study can be used as an input or reference to the development of the program of courses, especially in the subject of animal ecology.Â Keywords:Animal ecology fieldtrip; Classification skills; Identification Skillsebird